2015
DOI: 10.1103/physrevb.91.134204
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale dynamics of a model glass-forming metallic liquid: Dynamical crossover, dynamical decoupling, and dynamical clustering

Abstract: The phase behavior of multi-component metallic liquids is exceedingly complex because of the convoluted many-body and many-elemental interactions. Herein, we present systematic studies of the dynamical aspects of a model ternary metallic liquid Cu40Zr51Al9 using molecular dynamics simulations with embedded atom method. We observed a dynamical crossover from Arrhenius to super-Arrhenius behavior in the transport properties (self diffusion coefficient, self relaxation time, and shear viscosity) bordered at Tx ∼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 90 publications
10
57
0
Order By: Relevance
“…Our finding, that the Stokes-Einstein relationship is violated well above 1.2 × T g , are supported by several empirical studies of metallic liquids [42][43][44]. Furthermore, an illuminating concurrent MD study of liquid Cu 40 Zr 51 Al 9 submitted very shortly after the original submission of the current work similarly found that the relation breaks down specifically at T A ≈ 2 × T g for that alloy as well [45]. Taken together, these results bolster our finding of Stokes-Einstein violation at T A to a broader range of materials It is important to note that the local violation of the Stokes-Einstein equation at T A does not signify the onset of strong glassy dynamics in Cu 64 Zr 36 .…”
Section: Dynamical Features Of Liquidsupporting
confidence: 84%
“…Our finding, that the Stokes-Einstein relationship is violated well above 1.2 × T g , are supported by several empirical studies of metallic liquids [42][43][44]. Furthermore, an illuminating concurrent MD study of liquid Cu 40 Zr 51 Al 9 submitted very shortly after the original submission of the current work similarly found that the relation breaks down specifically at T A ≈ 2 × T g for that alloy as well [45]. Taken together, these results bolster our finding of Stokes-Einstein violation at T A to a broader range of materials It is important to note that the local violation of the Stokes-Einstein equation at T A does not signify the onset of strong glassy dynamics in Cu 64 Zr 36 .…”
Section: Dynamical Features Of Liquidsupporting
confidence: 84%
“…Examples include a structural signature of dynamical slowdown as well as the liquid fragility in metallic glass-forming liquids, [26][27][28][29][30][31][32] anomalous thermal contraction of metallic melts in the nearest-neighbor shell, [33][34][35] possible crystallike order in MGs/liquids, [36][37][38][39] a fractal structure model of MGs, [40][41][42] advanced algorithms (such as machine learning methods) to efficiently characterize the structural basis of flow defects and dynamical slowdown in amorphous materials, 43,44 and a new structure parameter that incorporates dynamic (atomic vibration) information beyond the description of static structure/ configuration. [45][46][47][48][49] Computational research has played a key role in formulating these ideas.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that in addition to monitoring structural ordering upon cooling to temperatures close to T g as discussed above, significant progress has been made very recently to understand the dynamical crossover of transport properties from Arrhenius to super-Arrhenius behavior, at high temperatures in liquids that are close to equilibrium (the crossover temperature is at~2T g for metallic liquids). 32,[78][79][80][81][82] In this regime, atomic correlations responsible for the onset of cooperative dynamics are being analyzed to provide a structural origin of the cross-over as well as a new perspective of the liquid fragility.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a deviation of the self relaxation time from high temperature Arrhenius behavior, i.e. Arrhenius crossover or dynamical onset, has been observed around similar temperatures in both neutron scattering measurements and molecular dynamics simulations 48 . However, the link between the self and the fast collective relaxation times is not trivial in such metallic liquids.…”
Section: Discussionmentioning
confidence: 99%